Implementasi Media Audio Visual Untuk Meningkatkan Hasil Belajar Gerak Dasar Dribbling Sepakbola Pada Mata Pelajaran PJOK - Ricky Alfredo Silaban; Jan Lengkong; Marnex Berhimpong (Peneliti.net, 2023)
The purpose of this study was to find out the results of learning dribbling in football usingAudio-visual media in physical education subjects in class XI students of SMA Negeri Tondano. This type of research is classroom action research, the number of samples in the study were 30 students, namely all students of class XI IPA 2. According to the results in dataProcessing carried out in cycle I, there were only 17 students who achieved learning completeness score (67,7 %), while 13 students had not achieved it (32,3 %). Furthermore, In cycle II there were 28 students who had passed (81,4 %) and 2 students had not achieved a completeness score (18,6 %). So that i can be concluded that the use of audio-visual media can improve dribbling learning outcomes in class XI students of SMA Negeri 2 Tondano.